APPLIED THEATRE RESEARCH: DISCOURSES IN THE FIELD - Gjaerum, Rikke Gurgens (European Scientific Journal, ESJ, 2014)
In this article, the author explores how discourses appear through the global field of ‘Applied Theatre Research’. The study includes a discourse analysis of books on ‘Applied Theatre’ worldwide and articles, mainly published in Applied Theatre Researcher and Research in Drama Education, since the year 2000. The discourse study is also based on 23 interviews. The study shows us that Applied Theatre Research is a discursive global field build up by the following six main discourses: The legitimation discourse, the ethics discourse, the effect discourse, the outsider-visitor discourse, the global economy discourse and the aesthetic discourse.